Modelling of phase equilibria of LiFePO4‐FePO4 olivine join for cathode material. (16th February 2019) - Phan, Anh Thu; Gheribi, Aïmen E.; Chartrand, Patrice
Abstract: A thermodynamic model for the FePO4 ‐LiFePO4 olivine join has been developed in order to provide support for the understanding of the charge transport behaviour within the cathode material during the battery operation. The Gibbs energy model for the olivine solution is based on the compound energy formalism with long‐range‐order and has been calibrated using the CALPHAD method, permitting the computation of phase equilibria by Gibbs energy minimization techniques. The model can simultaneously reproduce the reported eutectoid reaction, the 3 low‐temperature miscibility gaps, the enthalpy of mixing, and the change of the voltage plateau with temperature during the delithiation process, in agreement with the available experimental data. The spinodal decomposition, which is possibly associated with fast charge transport within the cathode material, involves up to two sub‐spinodal decompositions. Hence, the unique low‐temperature miscibility gap of this system is considered as a blend of the two sub‐miscibility gaps.